Hepatocellular Carcinoma–Circulating Tumor Cells Expressing PD‐L1 Are Prognostic and Potentially Associated With Response to Checkpoint Inhibitors - Paul Winograd; Shuang Hou; Colin M. Court; Yi‐Te Lee; Pin‐Jung Chen; Yazhen Zhu; Saeed Sadeghi; Richard S. Finn; Pai‐Chi Teng; Jasmin J. Wang; Zhicheng Zhang; Hongtao Liu; et al. (Hepatology Communications, 2020)
Hepatocellular carcinoma (HCC) is a leading cause of mortality. Checkpoint inhibitors of programmed cell death protein‐1 (PD‐1) and programmed death‐ligand 1 (PD‐L1) have shown great efficacy, but lack biomarkers that predict response. Circulating tumor cells (CTCs) have promise as a liquid‐biopsy biomarker; however, data on HCC CTCs expressing PD‐L1 have not been reported. We sought to detect PD‐L1‐expressing HCC‐CTCs and investigated their role as a prognostic and predictive biomarker. Using an antibody‐based platform, CTCs were enumerated/phenotyped from a prospective cohort of 87 patients with HCC (49 early‐stage, 22 locally advanced, and 16 metastatic), 7 patients with cirrhosis, and 8 healthy controls. Immunocytochemistry identified total HCC CTCs (4′,6‐diamidino‐2‐phenylindole–positive [DAPI+]/cytokeratin‐positive [CK+]/clusters of differentiation 45–negative [CD45−]) and a subpopulation expressing PD‐L1 (DAPI+/CK+/PD‐L1+/CD45−). PD‐L1+ CTCs were identified in 4 of 49 (8.2%) early‐stage patients, but 12 of 22 (54.5%) locally advanced and 15 of 16 (93.8%) metastatic patients, accurately discriminating early from locally advanced/metastatic HCC (sensitivity = 71.1%, specificity = 91.8%, area under the receiver operating characteristic curve = 0.807; P < 0.001). Compared to patients without PD‐L1+ CTCs, patients with PD‐L1+ CTCs had significantly inferior overall survival (OS) (median OS = 14.0 months vs. not reached, hazard ratio [HR] = 4.0, P = 0.001). PD‐L1+ CTCs remained an independent predictor of OS (HR = 3.22, P = 0.010) even after controlling for Model for End‐Stage Liver Disease score (HR = 1.14, P < 0.001), alpha‐fetoprotein (HR = 1.55, P < 0.001), and overall stage/tumor burden (beyond University of California, San Francisco, HR = 7.19, P < 0.001). In the subset of 10 patients with HCC receiving PD‐1 blockade, all 5 responders demonstrated PD‐L1+ CTCs at baseline, compared with only 1 of 5 nonresponders, all of whom progressed within 4 months of starting treatment. Conclusion: We report a CTC assay for the phenotypic profiling of HCC CTCs expressing PD‐L1. PD‐L1+ CTCs are predominantly found in advanced‐stage HCC, and independently prognosticate OS after controlling for Model for End‐Stage Liver Disease, alpha‐fetoprotein, and tumor stage. In patients with HCC receiving anti‐PD‐1 therapy, there was a strong association with the presence of PD‐L1+ CTCs and favorable treatment response. Prospective validation in a larger cohort will better define the utility of PD‐L1+ CTCs as a prognostic and predictive biomarker in HCC.